Biocompatible PCL/PLGA/Polypyrrole Composites for Regenerating Nerves - Ferreira, Cristina Lorenski; Valente, Cristhiane Alvim; Zanini, Mara Lise; Sgarioni, Bruna; Ferreira Tondo, Pedro Henrique; Chagastelles, Pedro Cesar; Braga, Jefferson; Campos, Maria Martha; Malmonge, José Antonio [UNESP]; de Souza Basso, Nara Regina (Wiley, 2019)
In the field of regenerative medicine, many studies have focused on regenerating peripheral nerves because clinical problems and functional loss of organs are affecting an increasing number of people. Biocompatible polymers can be potentially used for producing biocompatible tubes in order to aid the regeneration of peripheral nerves. This study aims to prepare polymeric composites based on polycaprolactone (PCL), poly (lactic-co-glycolic acid) (PLGA), and polypyrrole fibers (PPy) capable of acting as a conduit for regenerating peripheral nerves. Polypyrrole is synthesized by oxidative chemical polymerization with p-toluenesulfonic acid monohydrate (PTSA) as a doping agent. PCL/PLGA blends (100:0, 90:10, 80:20, and 70:30) (m/m) and PCL/PLGA composites with 10% PPy fibers were prepared by the solvent casting method. PPy with a diameter of 88–974 nm showed electrical conductivity of 2.0 × 10 −1 S cm −1 . The nontoxic composite films with hydrophilic and porous surfaces presented a thermal stability and degradation period that were suitable for potential use in the regeneration of peripheral nerves.
Keywords: composites; conducting polymers; poly (lactic-co-glycolic acid); polycaprolactone; polypyrrole